Handbook on Information Technologies for Education and Training
XXVIII, 465 p.
Keywords: The handbook's goal is to enable the reader to gain a deep understanding of past, current and future research and applications in the field of educational technology. The reader will gain an in-depth understanding of complex theories, strategies, concepts, and methods relating to the design, development, implementation, and evaluation of educational technologies. Because it combines both the present experience in the field and the vision of its emerging directions, the handbook will be a comprehensive guide for researchers and practitioners working with educational technologies. All the chapters of the second edition are newly written, the handbook therefore presents the latest developments in the field.